Therapeutic Potential of Hydroxysafflor Yellow A on Cardio-Cerebrovascular Diseases - Bai, Xue; Wang, Wen-Xiao; Fu, Rui-Jia; Yue, Shi-Jun; Gao, Huan; Chen, Yan-Yan; Tang, Yu-Ping (Frontiers in Pharmacology, 2020)
The incidence rate of cardio-cerebrovascular diseases (CCVDs) is increasing worldwide, causing an increasingly serious public health burden. The pursuit of new promising treatment options is thus becoming a pressing issue. Hydroxysafflor yellow A (HSYA) is one of the main active quinochalcone C-glycosides in the florets of Carthamus tinctorius L., a medical and edible dual-purpose plant. HSYA has attracted much interest for its pharmacological actions in treating and/or managing CCVDs, such as myocardial and cerebral ischemia, hypertension, atherosclerosis, vascular dementia, and traumatic brain injury, in massive preclinical studies. In this review, we briefly summarized the mode and mechanism of action of HSYA on CCVDs based on these preclinical studies. The therapeutic effects of HSYA against CCVDs were presumed to reside mostly in its antioxidant, anti-inflammatory, and neuroprotective roles by acting on complex signaling pathways.